1997
DOI: 10.1093/oxfordjournals.eurheartj.a015310
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of atrial fibrillation to sinus rhythm and rate control by digoxin in comparison to placebo

Abstract: Intravenous digoxin offers no substantial advantages over placebo in recent onset atrial fibrillation with respect to conversion, and provides weak rate control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 19 publications
2
61
0
1
Order By: Relevance
“…Digoxin exerts only a transient rate-slowing effect in patients with recent-onset AF, 378 perhaps as a result of a vagotonic effect on the AV node. In contrast to its limited negative chronotropic effect in patients with paroxysmal AF, digoxin is moderately effective in those with persistent AF, particularly when HF is present.…”
Section: Classmentioning
confidence: 99%
See 1 more Smart Citation
“…Digoxin exerts only a transient rate-slowing effect in patients with recent-onset AF, 378 perhaps as a result of a vagotonic effect on the AV node. In contrast to its limited negative chronotropic effect in patients with paroxysmal AF, digoxin is moderately effective in those with persistent AF, particularly when HF is present.…”
Section: Classmentioning
confidence: 99%
“…Digoxin has few adverse effects after acute administration in therapeutic doses, aside from AV block and increased ventricular ectopy, but all manifestations of digitalis toxicity are dose related. 375,378,494,505,526,530,540,542 8.1.5.5.6. DISOPYRAMIDE.…”
Section: Less Effective or Incompletely Studied Agents For Cardioversmentioning
confidence: 99%
“…300 Amiodarone may control rate and rhythm (LOE 1), 301 but significant complications were described in placebocontrolled trials: the risk of adverse events was 26.8% as a pooled estimate, and the most common side effects encountered were phlebitis, bradycardia, and hypotension (LOE 1). 301 Digoxin is not effective for cardioversion (LOE 1), [302][303][304] but in some studies it has been shown to have moderate rate controlling properties (LOE 1). 297,303,304 Rhythm Control of Atrial Fibrillation.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…301 Digoxin is not effective for cardioversion (LOE 1), [302][303][304] but in some studies it has been shown to have moderate rate controlling properties (LOE 1). 297,303,304 Rhythm Control of Atrial Fibrillation. Ibutilide has consistently been more effective in converting atrial fibrillation to sinus rhythm when compared with placebo (LOE 1), [305][306][307] or other antiarrhythmic drugs (LOE 1: sotalol, 308 procainamide, 309 and amiodarone, 310 ) and equal to other drugs (LOE 1: flecainide 311 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…136 Available evidence suggests that digitalis, 158 though effective, is the least potent and has the slowest onset of action of the available pharmacological options for ventricular rate control. In patients with clinical evidence of congestive heart failure, greater caution should be exercised in use of calcium channel and ␤-blocking agents because of their recognized negative inotropic properties and because in trials of efficacy, patients with congestive heart failure were usually excluded.…”
Section: Atrial Fibrillation/fluttermentioning
confidence: 99%